Clinical, economic, and humanistic burden of community acquired pneumonia in Europe: a systematic literature review - Eleana Tsoumani; John A Carter; Stina Salomonsson; Jennifer M Stephens; Goran Bencina (Taylor & Francis Group, 2023)
Background Community-acquired pneumonia (CAP) is an infectious lung inflammation contracted outside the hospital. CAP is a leading cause of death among young children, elderly, and immunocompromised persons. Incidence can reach 14 cases/1,000 adults. Up to 50% of cases require inpatient hospitalization. Mortality is 0.7/1,000 cases or 4 million deaths per year. We sought to summarize multi-dimensional burden of CAP for selected European countries. Methods We conducted a systematic literature review of literature published from 2011 to 2021 whereby we sought information pertaining to the epidemiologic, clinical, economic, and humanistic burden of CAP. Findings were summarized descriptively. Results CAP incidence in Europe is variable, with the highest burden among those of advanced age and with chronic comorbidities. Etiology is primarily bacterial infection with Streptococcus pneumoniae being the most frequently implicated. Direct medical costs are primarily attributable to inpatient stay, which is exacerbated among high-risk populations. Higher mortality rates are associated with increasing age, the need for inpatient hospitalization, and antibiotic resistance. Conclusions A better understanding of CAP is needed, specifically the economic and quality of life burden on patients and caregivers. We recommend further assessments using population-level and real-world data employing consistent disease definitions.